THE EFFECT OF PERCEIVED ORGANIZATIONAL SUPPORT AND JOB INVOLVEMENT ON THE ORGANIZATIONAL COMMITMENT OF FACULTY LECTURERS AT MUHAMMADIYAH UNIVERSITIES IN JABODETABEK - Muhammad Yusuf; Fajar Adi Prakoso (Jurnal Ekonomi Trisakti, 2022)
This research aimed to analyze the effect of perceived organizational support and job involvement on the organizational commitment of faculty lecturers at Muhammadiyah Universities in Jabodetabek. The research method used in this research is associated with a quantitative population of 1,402 faculty lecturers at Muhammadiyah Universities in Jabodetabek. A sample of 178 respondents and the sampling technique used in random sampling. The analytical method used is multiple linear regression. Based on the results of this research, it can be found that (1) Perceived organizational support has a positive and significant effect on organizational commitment. Therefore, to increase the permanent organizational commitment of Muhammadiyah University in Jabodetabek, the perceived organizational support must also be increased, and (2) organizational involvement has a positive and significant effect on commitment. Therefore, to increase the permanent organizational commitment of Muhammadiyah University in Jabodetabek, work involvement must also be increased.